Agile framework to manage virtual project teams in Singapore software industry - Bo Bo Hein (Nanyang Technological University, 2023)
In the fast-changing global arena, organisations are transforming into thinking-big-starting-small agile-based operations to perform better responsiveness to the charge at which various talent pools are required to self-organise, collaborate, and co-work. The primary process and management are crucial for software development in the complex process. Resource management in Agile is prior to the success of projects in the real world. Agile methodology has gained popularity as an approach emphasising collaboration, flexibility, and iterative development. This multiple qualitative case study dissertation explored software development manager’s strategies in adopting Agile methodology for virtual project teams. The dissertation focused on the tenets of Agile methodology, which prioritise individual interaction, working software, and collaboration over traditional methods that emphasise tools, documentation, and contracts. When virtual project teams cross borders, policymakers are concerned about data protection and security requirements. To successfully implement Agile methodology for virtual project teams, software development managers used various strategies, including communication and collaboration tools, virtual team-building activities, and training and development programs for team members. The study found that effective communication was essential for keeping team members connected and motivated and that virtual team-building activities effectively built trust and fostered collaboration among team members. The data for this qualitative multiple case study were collected through face-to-face interviews with project managers and operations managers with experience implementing Agile methodology for virtual project teams. In addition to the discussions, the study also involved a review of project-tracking documentation and tools, such as software development plans, project schedules, and team collaboration platforms. The data analysis process for this study involved inductive coding of the transcribed interviews. The researcher then used an iterative data reduction process, data display, and conclusion drawing to refine the coding scheme and identify more specific categories. The use of multiple data sources, including face-to-face interviews and project-tracking documentation and tools, helped ensure the study finding’s validity and reliability. The results of this qualitative multiple case study suggest that there are effective strategies for adopting Agile methodology in the context of virtual project teams. In this research, challenges will be critical analyses through People, Process, Policy, and Technology lenses and provide recommendations for better productivity of organisations. Virtual teams have become increasingly popular over the last decade, and the COVID-19 pandemic has accelerated this trend. Agile frameworks are well-suited to managing virtual teams, but managers must be mindful of the unique challenges that virtual teams face. Effective communication, mental well-being, team bonding, data protection, and security are all critical factors that must be addressed. Virtual teams must have clear roles and responsibilities, and managers must monitor progress and meet deadlines. Overall, the findings of this study suggest that the effective adoption of Agile methodology for virtual project teams requires a combination of coaching and training, incremental implementation, and proactive management of communication effectiveness. By adopting these strategies, software development managers can increase the financial stability of software engineers and accelerate the successful development of information systems, ultimately enriching human lives.